HYDRATE MITIGATION FOR DEEP WATER AND LONG DISTANCE PIPELINE – FLOW ASSURANCE APPROACH - Riesto Mundi Karono (Scientific Contributions Oil and Gas, 2015)
The existence of gas hydrates is well known in the oil and gas production industry. The components are dominated by methane and naturally occur in deep marine sediment along continental margins. Although hydrates may be of potential benefi t both as a hydrocarbon resource and as a mean of storing and transmitting natural gas, traditionally their presence is considered to be an operational and a safety problem. They can form at the pressures and temperatures found in natural gas and oil pipelines causing blockages, especially when temperature falls signifi cantly, such as when closing in a well or fl owing gas through a choke. This could deliver a serious potential problem for oil and gas offshore production either for its equipment or personnel. Besides the variation of gas rate to avoid hydrates forming, currently there are two methods that have been used widely to prevent hydrates formation in production pipelines - thermal insulation and chemical inhibitor. Each method has its own benefits. PIPESIM software application can be used to evaluate both mitigation methods and to then fi nd which is the best scenario based on lowest cost, shortest period of application and less adversity.